The safety and efficacy of PD-1 inhibitors in patients with advanced cancers and HIV/AIDS in China - Xiong, Yu; Mo, Pingzheng; Yan, Yajun; Wang, Shan; Zhuang, Ke; Ma, Zhiyong; Chen, Xiaoping; Deng, Liping; Xiong, Yong; Deng, Di; Zhang, Yongxi (Frontiers in Oncology, 2023)
Purpose-Immunotherapy has revolutionized cancer therapy, becoming the standard of care for various malignancy treatments. Human immunodeficiency virus (HIV) patients, however, are an underserved group with limited access to clinical trials and cancer therapy. This study was to evaluate the safety and efficacy of programmed cell death 1 (PD - 1) inhibitors in patients with advanced cancer and HIV / acquired immunodeficiency syndrome (AIDS). Methods and Materials-We performed a prospective, open-label, nonrandomized, phase 1 single center study. Patients with advanced cancer and HIV / AIDS received the treatment of PD - 1 inhibitors (camrelizumab, 200 mg, administered intravenously every 3 weeks), along with combination antiretroviral therapy (cART) for HIV. Results-Sixteen participants (12 men and 4 women; median age, 46.5 (29 - 78) years) were enrolled; 1 had non - Hodgkin lymphoma (NHL), and 15 had non - AIDS - defining cancers. Safety was observed over 130 cycles of treatment with camrelizumab. Most treatment-emergent adverse events at least possibly attributed to camrelizumab were grade 1 or 2, including reactive cutaneous capillary endothelial proliferation (RCCEP) (9 participants), hearing loss (1 participant), hypophysitis (1 participant). 3 participants experienced hemorrhage due to poor performance status. HIV was controlled in all participants. Best tumor responses included 3 complete response, 5 partial response, 2 stable disease, and 6 progressive disease. The 2 years progression-free survival (PFS) was 67.0 % (95 % CI: -0.05, 0.00) and overall survival (OS) was 55.3 % (95 % CI: -0.05, 0.01) for the 16 patients who had received camrelizumab. Conclusions-This study demonstrates that camrelizumab treatment in patients with advanced cancers and HIV / AIDS was feasible and the clinical outcomes were acceptable.